KEABSAHAN AKAD DALAM TRANSAKSI GO-FOOD MENURUT ISLAM - Mahfud, Moh (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2021)
The necessities and the increasing life demand make almost everyone want to do everything simple and instantly. So that it pops a new breakthrough in meeting these living needs. One of them is the Go-Food service made by PT. Aplikasi Karya Anak Bangsa which is part of the Go-Jek Application. Go-Food services make it easy for anyone to order food instantly, even while lying down at home. But the problem is when it comes into conflict with Shariah rules regarding transactions using this service, is it legal or not? This is the background of writingIDEALITA | Sekolah Tinggi Agama Islam Al Falah Pamekasan 36this research that the focus of the research is the gatheringof several contracts and there are elements of usury (riba) in this Go-Food. The purpose of this study is to find out the validity of the contract in Go Food transactions according to Islam, with a research method based on normative juridical approach with descriptive specifications with data in from of secondary data. The data collection methods used are library research with qualitative analysis method. The results and discussion of the research indicate that the contract in Go-Food transactions is appropriate to the Islamic Rules based on its sources, namely the Holy Qur’an, hadith, and the opinions of scientists in the trusted books.